Psychiatric morbidity in Northern Jordan: a ten-year review - Zaidan, Z (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2000)
OBJECTIVE: To study the psychiatric morbidity in the northern part of Jordan and to determine the frequency distribution of various psychiatric disorders, for planning services. METHOD: All records of 2,335 psychiatric patients attending the only psychiatric clinic in Northern part of Jordan during a ten-year period from 1984 to 1993 were extensively reviewed and subjected to computerized analysis. Diagnosis was made as per ICD-9. RESULTS: Out of the 2335 patients who attended the clinic, 55% were males and 45% were females. Those in the age group 25–44 recorded the maximum attendance. Among the male attendees of the clinic, schizophrenia was the commonest diagnosis(19.9%), while among females, affective disorders were the commonest(15.9%). CONCLUSION: Schizophrenia was found to be the commonest diagnosis in general among attendance of the clinic for the ten-year research period, while anxiety disorders were the commonest diagnosis among attendance of the clinic for the year 1993.